The coronavirus and center-peripheral relations in the economies of the European Union - Krzysztof Jasiecki (International Journal of Management and Economics, 2022)
From the perspective of the diversity of capitalism and that of economic sociology, the article deals with the issue of center-peripheral relations as one of the key dimensions of economic diversification that determines the development opportunities of the European Union. The collapse of the convergence processes during the 2008-2010 financial crisis revealed the separateness of development trajectories of various countries and geographical regions of the EU. Without reversing this phenomenon and working out new mechanisms of development convergence and institutions supporting them, the process of European integration will enter further structural crises that may lead to the disintegration of the EU. Various classifications of the core and of the peripheries of the euro area are characterized, within which several types of countries are identified with different economic characteristics (countries of the Northern core and of the Southern peripheries of the euro area, different types of peripheries in Southern Europe and in Central and Eastern Europe, the internal core and the external core or the outer core, and the internal peripheries and the external peripheries, as well as the super-peripheries including candidates or potential candidates to join the EU). The COVID-19 crisis has an asymmetric impact on the economic situation of the Member States. As with other crises, this impact will be the result of the interconnection of the prior state of economies, structural differences in growth patterns, and responses to new challenges brought about by the pandemic. Also, the consequences of the pandemic for the reconfiguration of center-peripheral relations in the EU are discussed, with a particular focus on the CEE.
Keywords: A14; A12; F15; P51; 650; The impact of the pandemic on the economic future of the EU; center-peripheral relations in the EU; the diversity of the trajectories of capitalism development in Europe; similarities and differences of the EU peripheries; new classifications of the core and of the peripheries